Clinical anatomy teaching: A promising strategy for anatomic education - Yujie Zhang; Zhenni Ji; Peizhi Zhou; Lihua Dong; Yao Chen (Heliyon, 2023)
Background: Human anatomy is a predominant course that helps medical students enhance their performance in other clinical curricula. However, it is difficult for students to learn the relationship between anatomy and diseases, since the traditional teaching modality of anatomy courses does not contain enough clinical contents. Clinical anatomy education merges clinical diagnosis and treatment into anatomy learning. This study seeks to determine whether systematic clinical anatomy teaching can improve students’ performance and interest in anatomy courses. Methods: This study was a retrospective study conducted at West China Medical School, Sichuan University. Medical students of the 8-year program who participated in the course “HUMAN MORPHOLOGY” in the academic years of 2014–2018 did not receive a systematic clinical anatomy course, while those in the academic years of 2018–2022 did. These two groups were involved to analyze their final examination. Then, a questionnaire for students in the academic year of 2021–2022 was conducted to assess their general satisfaction and opinions on the usefulness and learning modalities of clinical anatomy courses. Results: Students who received systematic clinical anatomy lessons performed significantly better than those who were not in the final examinations. The average grades were 73.64 and 79.90 in the 3rd semester of medicine (p < 0.0001) and 75.70 and 82.18 in the 4th semester of medicine (p < 0.0001) before and after 2018, respectively. The response rate of the questionnaire was 77.78%, and most of the students agreed that the clinical anatomy lessons were satisfactory, with 40 out of 71 (56.34%) strongly agreeing and 26 out of 71 (36.62%) agreeing. Conclusion: Clinical anatomy education should be more emphasized and merged into the gross anatomy curriculum owing to the better performance in the final examination and high rate of satisfaction.